White mythologies - Young, Robert (London Routledge, 2004)
We must, many now argue, `get back' to history. but which one? History has always been a problematical concept in Western theory, particularly for Marxism. In the wake of postmodernism, its status has become ever less certain. Is it possible to write history that avoids the trap of Eurocentrism?
Includes bibliographical references (p. 249-266) and index.
Keywords: History--Philosophy.